PENGARUH PENGALAMAN PENDIDIKAN DAN LATIHAN, MASA KERJA, DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMK NEGERI DI KECAMATAN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research is conducted to discover the Influence of Education and Training Experience, Tenure, and the Leadership on the Working Performance of Vocational School Teachers in Wonosobo regency, for public and private schools in 2014/2015 academic year.This research is a correlative study to find out the relationships among variables indicated by the correlation coefficient. The data were taken from the population of vocational teachers in Wonosobo, Central Java. The research data were executed using proportional random sampling. The data collection is managed using questionnaire instruments. These data were analysed using multiple regression analysis with three predictors. The hypotheses tests were handled using F-test or ANOVA and using partial test (t-test) respectively. The data were tested using the prerequisite tests. They were normality test, linearity test and multicollinearity test with a significance level of 5%.Based on the results of this study, the writer may conclude that, (1) there is a positive and significant effect of educational and training experience, tenure and leadership on the working performance of vocational school teachers in Wonosobo, (2) there is a positive and significant effect of educational and training experience on the working performance of vocational school teachers in Wonosobo, (3) there is a positive and significant effect of tenure on the working performance of vocational school teachers in Wonosobo, (4) there is a positive and significant effect of leadership on the working performance of vocational school teachers in Wonosobo. All of the effective contribution percentage is 60.5 %. The positive influence means,the higherÂ  education and training experience, tenure, leadership, the higher the influence forwards the teacher working performance.